The American way : government and politics in the United States - Robins, L. J. (London : Longman, 1985)
A series of essays on aspects of American history and politics, such as the party systems, the presidency, and the nuclear freeze movement.
Includes bibliographies and index.
Keywords: United States -- Politics and government; United States -- Politics and government